2000
DOI: 10.2149/tmh1973.28.15
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline resistant and polymyxin B sensitive vibrio cholerae O1 E1 tor isolated from the recent epidemics.

Abstract: By examining 99 Vibrio cholerae 01 isolates from cholera epidemics in a variety of areas in Laos in 1998, we found two unusual characteristics of the organisms. All except 4 isolates were moderately resistant to tetracycline without having plasmids, and susceptibilities to the other drugs were as expected. Eleven isolates showed the same level of susceptibility to polymyxin B as classical V. cholerae 01. With the exception of 4 tetracycline-susceptible strains, all the isolates were resistant to or poorly sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…In the Lao People's Democratic Republic (Lao PDR), Vibrio cholerae isolates are collected at the Center for Laboratory and Epidemiology, and their cholera toxin and hemolysin production are studied, as well as their susceptibility to phages and antimicrobials. In the period between 1993 and 2000, although the pathogens were sensitive to the therapeutic antimicrobials as expected until 1996, a change in the drug sensitivity pattern started in 1998 after a period without cholera (13,17,20). Strains isolated after 1997 were found to be moderately resistant to tetracycline and chloramphenicol and highly resistant to trimethoprim-sulfamethoxazole (20).…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…In the Lao People's Democratic Republic (Lao PDR), Vibrio cholerae isolates are collected at the Center for Laboratory and Epidemiology, and their cholera toxin and hemolysin production are studied, as well as their susceptibility to phages and antimicrobials. In the period between 1993 and 2000, although the pathogens were sensitive to the therapeutic antimicrobials as expected until 1996, a change in the drug sensitivity pattern started in 1998 after a period without cholera (13,17,20). Strains isolated after 1997 were found to be moderately resistant to tetracycline and chloramphenicol and highly resistant to trimethoprim-sulfamethoxazole (20).…”
mentioning
confidence: 72%
“…Among a collection of 284 V. cholerae O1 biotype El Tor strains recovered from cholera patients from 1993 to 2000, 50 strains were included in the present study for further analysis. The various phenotypic characteristics of the strains were studied previously (13,17,20,25). Before PCR analysis, antibiotic resistance was confirmed in these isolates by MIC determination, and the results were compared with the initial MIC results (13,17,20).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An epidemic or outbreak due to O1 strains resistant to TC is recognized very infrequently. In the last decade, O1 Ogawa strains resistant to TC were isolated from epidemics in south-ern Thailand in 1997 and 1998 (22) and in Laos in 1998 (16). The strains isolated from an epidemic in southern Thailand in 1998 were included in this study, and they showed the profile A1 (Table 3).…”
Section: Resultsmentioning
confidence: 99%